1993
DOI: 10.1093/milmed/158.8.563
|View full text |Cite
|
Sign up to set email alerts
|

Primary Closure of Gunshot Wounds Caused by High-Velocity Rifles

Abstract: Sixty gunshot injuries in 48 patients were treated in Mobile Surgical Hospital (30-bed capacity) of the Mountain and Commando Brigade in Hakkari, Türkiye, between May 1990 and May 1991. The David Sisk method was used for the classification of the injuries. Eleven type 1 injuries were treated conservatively, 39 type 2 and 10 type 3 injuries were treated by extensive debridement with suction drainage and primary closure. No infection was seen in type 1 injuries. The infection rate was 2.56% in type 2 and 20% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nuzumlali et al [6] treated 60 gunshot wounds caused by high velocity rifles by primary closure and found that primary closure following extensive debridement and suction drainage was effective. The infection rate ranged from 2.5% to 20% depending on wound grades [6].…”
Section: Delayed Union Was Observed In 11 Cases (141%) the Total Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuzumlali et al [6] treated 60 gunshot wounds caused by high velocity rifles by primary closure and found that primary closure following extensive debridement and suction drainage was effective. The infection rate ranged from 2.5% to 20% depending on wound grades [6].…”
Section: Delayed Union Was Observed In 11 Cases (141%) the Total Inmentioning
confidence: 99%
“…The infection rate ranged from 2.5% to 20% depending on wound grades [6]. Benson et al [7] prospectively studied 82 open fractures and found that the timing of wound closure did not affect the infection rate.…”
Section: Delayed Union Was Observed In 11 Cases (141%) the Total Inmentioning
confidence: 99%